Effect of PM2.5 chemical constituents on atmospheric visibility impairment. (4th May 2018) - Khanna, Isha; Khare, Mukesh; Gargava, Prashant; Khan, Anwar Ali
ABSTRACT: PM2.5 sampling was conducted at a curbside location in Delhi city for summer and winter seasons, to evaluate the effect of PM2.5 and its chemical components on the visibility impairment. The PM2.5 concentrations were observed to be higher than the National Ambient Air Quality Standards (NAAQS), indicating poor air quality. The chemical constituents of PM2.5 (the water-soluble ionic species SO4 2-, NO3 −, Cl −, and NH4 +, and carbonaceous species: organic carbon, elemental carbon) were analyzed to study their impact on visibility impairment by reconstructing the light extinction coefficient, bext . The visibility was found to be negatively correlated with PM2.5 and its components. The reconstructed bext showed that organic matter was the largest contributor to bext in both the seasons which may be attributed to combustion sources. In summer season, it was followed by elemental carbon and ammonium sulfate; however, in winter, major contributions were from ammonium nitrate and elemental carbon. Higher elemental carbon in both seasons may be attributed to traffic sources, while lower concentrations of nitrate during summer, may be attributed to volatility because of higher atmospheric temperatures. Implications : The chemical constituents of PM2.5 that majorly effect the visibility impairment are organic matter and elemental carbon, both of which are products of combustion processes. Secondary formations that lead to ammonium sulfate and ammonium nitrate production also impair the visibility.